An Overview of Robot Operating System Forensics - Basheer, Mawj Mohammed; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2019)
Autonomous technologies have been rapidly replacing the traditional manual intervention nearly in every aspect of our life. These technologies essentially require robots to carry out their automated processes. Nowadays, with the emergence of industry 4.0, robots are increasingly being remote-controlled via client-server connection, which creates uncommon vulnerabilities that allow attackers to target those robots. The development of an open source operational environment for robots, known as Robot Operating System (ROS) has come as a response to these demands. Security and privacy are crucial for the use of ROS as the chance of a compromise may lead to devastating ramifications. In this paper, an overview of ROS and the attacks targeting it are detailed and discussed. Followed by a review of the ROS security and digital investigation studies. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: Cyber-security; digital forensics; robot operating system; vulnerabilities